2002
DOI: 10.5395/jkacd.2002.27.4.363
|View full text |Cite
|
Sign up to set email alerts
|

The influence of moisture control on bond strength of composite resin treated with self-etching adhesive system

Abstract: A goal of restorative dentistry is to develope adhesive restorative materials that are durable and provide an effective seal at the restoration/ tooth interface. To achieve this purpose, many enamel-dentin bonding systems were introduced and improved in a new formula. These new adhesive materials not only attempt to improve the quality of the bond, but also simplifying the clinical procedures.Most recent innovative changes of bonding concept are the "total-etch"and "wet-bonding"techniques, and these methods ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Acetone and ethanol are the most popular solvents used for the adhesive agents. Usually acetone is more volatile than ethanol and it is easier to remove after application, but there is less chance for ideal handling and this resulted in more technique sensitivity 10. For the etch-and-rinse system, wet adhesive is essential for preventing the collapse of the exposed collagen fibers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetone and ethanol are the most popular solvents used for the adhesive agents. Usually acetone is more volatile than ethanol and it is easier to remove after application, but there is less chance for ideal handling and this resulted in more technique sensitivity 10. For the etch-and-rinse system, wet adhesive is essential for preventing the collapse of the exposed collagen fibers.…”
Section: Introductionmentioning
confidence: 99%
“…For the etch-and-rinse system, wet adhesive is essential for preventing the collapse of the exposed collagen fibers. However, the acid in the self-etching system is milder than phosphoric acid, and if the adhesive agent is diluted by the excess water on the adhesive surface, it may reduce the bond strength of the self-etching system 9,10. On the contrary, Werner and Tani reported that the dentin wetness and relative humidity did not affect the bond strength of the one-step self-etching adhesive systems 11…”
Section: Introductionmentioning
confidence: 99%
“…Acetone and ethanol are the most popular solvents used for the adhesive agents. Usually acetone is more volatile than ethanol and it is easier to remove after application, but there is less chance for ideal handling and this resulted in more technique sensitivity 11. Residual solvents may compromise the polymerization of adhesives and also directly affect the bond integrity, providing defects within the polymerized adhesive and pathways for nanoleakage 12-14.…”
Section: Introductionmentioning
confidence: 99%
“…Recently developed adhesives systems, such as the "one-bottle" system or the "self-etching primer" system, have been shown to be resistant to salivary contamination (El-Kalla & García-Godoy, 1997;Hitmi & others, 1999). Furthermore, in addition to simplifying the bonding technique, self-etching primer eliminates the rinsing and drying steps that reduce the possibility of overwetting or overdrying, both of which can negatively influence adhesion (Milia, Lallai & García-Godoy, 1999;Jin, Kim & Park, 2002). These dentin bonding agents have a reduced number of components and application steps, and this reduces the risk of saliva contamination in the field of operation.…”
Section: Introductionmentioning
confidence: 99%